Challenges in the Valorization of the Funerary Heritage; Experiences in the Municipal Cemetery of Murcia (Spain) - Gabriel López-Martínez; Klaus Schriewer (Heritage, 2022)
The cemetery is a cultural landscape that represents themes of great relevance to interpret the structure of a society, roles, and hierarchies, as a reflection of its social life. The cemetery gathers a whole symbolic universe where local social histories are represented, beyond the history of art and the architectural aspect. As a heritage element, the cemetery shows us the socio-cultural changes of a territory: religious questioning, changes linked to the family, individualization of contemporary society or broader questions about socio-economic structure. This article presents the experience conducted during the last 6 years in the Cemetery “Nuestro Padre Jesús” in Murcia (Spain), through a collaboration among the Sociedad Murciana de Antropolgía (SOMA), the University of Murcia and the Municipality of Murcia, developing the project “Funerary Cultures”, whose main objective is to promote the heritage, cultural and historical values of the funerary culture. Specifically, as a result of this teaching innovation experience, the six thematic guides to visit the cemetery are presented as an experience of patrimonialization of elements of the cemetery and its consequent selection and consensus exercise to determine what was considered as heritage in the context of the cemetery. Finally, a proposal of a systematic process in the valuation and selection of the material objects in the cemetery is presented; this proposal allows us to establish a debate on what considerations to take into account when considering the relationship between cultural heritage and the cemetery as a cultural landscape in permanent transformation.